2004
DOI: 10.1063/1.1723694
|View full text |Cite
|
Sign up to set email alerts
|

Optically-induced magnetization of CdMnTe self-assembled quantum dots

Abstract: We demonstrate that resonant excitation of CdMnTe self-assembled quantum dots creates an ensemble of spin-polarized magnetic polarons at B=0 T. The strong spatial confinement characteristic of quantum dots significantly increases the stability of magnetic polarons so that the optically induced spin alignment is observed for temperatures > 120 K. *Author to whom the correspondence should be addressed: electronic mail: seb@physics. Incorporation of magnetic ions into semiconductor QDs offers the possibility of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 20 publications
4
77
1
Order By: Relevance
“…A question remains as to why the zero magnetic field splitting is observed here while it was not seen in the optical measurements of Ref. [16,17]. This however can be understood by the fact that once current begins flowing through the dot, a feedback mechanism sets in where spin polarization of the current enhances the polarization of Mn spins which in turn enhances the polarization of the current.…”
Section: Gaasmentioning
confidence: 62%
“…A question remains as to why the zero magnetic field splitting is observed here while it was not seen in the optical measurements of Ref. [16,17]. This however can be understood by the fact that once current begins flowing through the dot, a feedback mechanism sets in where spin polarization of the current enhances the polarization of Mn spins which in turn enhances the polarization of the current.…”
Section: Gaasmentioning
confidence: 62%
“…6 Using ferromagnetic EuO quantum structures, it is possible to produce spin-polarized currents reaching 100%, 7 which is larger than the theoretical limit for conventional semiconductor quantum structures. 8 Light-induced magnetic order 9 in materials is also an interesting effect for spintronic applications, 10,11 which has not yet been explored in EuX.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in the bulk structures, adding a single carrier in a magnetic QD can have important ramifications. An extra carrier can both strongly change the total carrier spin and the temperature of the onset of magnetization which we show can be further controlled by modifying the quantum confinement and the strength of Coulomb interactions.We study the magnetic ordering of carrier spin and magnetic impurities in (II,Mn)VI QDs identified as a versatile system to demonstrate interplay of quantum confinement and magnetism [4,5,6,15,16,17,18]. Because Mn is isoelectronic with group-II elements it does not change the number of carriers which in QDs are controlled by either chemical doping or by external electrostatic potential applied to the metallic gates.…”
mentioning
confidence: 99%
“…We predict a series of electronic spin transitions which arise from the competition between the many-body gap and magnetic thermal fluctuations. Magnetic doping of semiconductor quantum dots (QDs) provides an interesting interplay of interaction effects in confined geometries [1,2,3,4,5,6,7,8] and potential spintronic applications [9]. In the bulk-like dilute magnetic semiconductors the carrier-mediated ferromagnetism can be photoinduced [10,11] and electrically controlled by gate electrodes [12], suggesting possible nonvolatile devices with tunable optical, electrical, and magnetic properties [9].…”
mentioning
confidence: 99%